EFFECT OF WORK DISCIPLINE AND SUPERVISION ON EMPLOYEE PERFORMANCE - Noto Susanto; Asep Suherman; Didi Sunardi (Asosiasi Dosen Muda Indonesia, 2024)
This research investigates the impact of discipline and work supervision on employee performance at PT. Inti Nomika Indonesia. The method used in this research is a quantitative approach with a descriptive emphasis. Samples were taken in a saturated manner, with 70 respondents. Data analysis used multiple regression analysis with SPSS 26.00. The research results show that work discipline positively and significantly influences employee performance. Work supervision also has a positive and significant influence on employee performance. Simultaneously, work discipline and work supervision have a positive and significant influence on employee performance. The regression equation shows that the relationship between the two variables and employee performance is solid, with a correlation coefficient of 0.823 and a coefficient of determination of 67.8%.